(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the knowledge, attitudes, and practices of healthcare workers regarding nutritional care at Tien Giang Psychiatric Hospital in 2025 and to analyze associated factors. Method: A cross-sectional study was conducted among 100 healthcare workers directly involved in patient care. Data were collected using a structured questionnaire based on Circular 18/2020/TT-BYT. Statistical analysis was performed using SPSS 22.0 software. Results: 40% of healthcare workers had satisfactory knowledge; 85% had a positive attitude; and 62% had satisfactory practices. Related factors included age, educational level, years of service, and participation in training (p < 0.05). Conclusion: Healthcare workers demonstrated moderate knowledge and positive attitudes but limited practice in nutritional care. Strengthening training and standardizing nutritional care procedures are urgently needed.